Robust Scheduling: An Empirical Study of Its Impact on Air Traffic Delays. (April 2017) - Lonzius, Marc Christopher; Lange, Anne
Highlights: We investigate the effect of robust scheduling strategies on delays. We further develop and empirically verify two theoretical concepts. We analyze more than 1 million flights and separate by carrier network type. Regression analyses show a significant delay impact of the analyzed strategies. This impact varies across airlines and with respect to the carrier network type. Abstract: We develop an econometric model to analyze the real-life impact of two robust scheduling approaches, namely limiting hub connectivity and implementing swap opportunities, based on a broad dataset of the U.S. domestic market. Our analysis is from a novel aircraft routing perspective. We confirm a delay-driving effect of direct hub connectivity and a delay-reducing effect of swap opportunities. Indirect hub connectivity provides airlines with another approach to limit delays. We furthermore contrast that the business model of Southwest Airlines cannot leverage the delay-reducing effects resulting from swap opportunities.